RANCANG BANGUN PORTAL OTOMATIS MENGGUNAKAN PENGENALAN PLAT NOMOR MENGGUNAKAN CAMERA - Setiawan Ardhana, Irgi; Pikkri, Muhammad; Febriansyah, Aan; Jasman Duli, Sirlus Andreanto (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2025)
Currently, every shopping center such as a mall must have good parking management, starting from recording incoming vehicles to recording exits based on certain rates charged to visitors. The increasing number of visitors coming to these parking areas will increase the busyness of parking operators. Therefore, a way is needed to help facilitate data collection of incoming and outgoing vehicles. Some devices used to facilitate parking data collection are by using computer devices, which have been widely applied for parking management both in shopping centers and offices. Data collection of vehicles entering and leaving the parking area, as well as calculations regarding the length of parking time and fees charged can be completed properly.